2011
DOI: 10.1007/s00425-010-1345-0
|View full text |Cite
|
Sign up to set email alerts
|

Histology and symplasmic tracer distribution during development of barley androgenic embryos

Abstract: The present study concerns three aspects of barley androgenesis: (1) the morphology and histology of the embryos during their development, (2) the time course of fluorescent symplasmic tracers’ distribution, and (3) the correlation between symplasmic communication and cell differentiation. The results indicate that barley embryos, which are developing via an androgenic pathway, resemble their zygotic counterparts with respect to their developmental stages, morphology and histology. Analysis of the distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Ferrie. of them is production of androgenic structures with varying regeneration abilities (Larsen et al 1991;Pretová et al 2006;Makowska et al 2015). In a model course of androgenesis, microspores develop into embryos similar to the zygotic ones (Sangwan and Sangwan-Norreel 1996;Wrobel et al 2011), however in practice, haploid cells may develop into a variety of structures. Among them are embryos with well-formed scutellum, root and shoot apical meristems and coleoptile.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrie. of them is production of androgenic structures with varying regeneration abilities (Larsen et al 1991;Pretová et al 2006;Makowska et al 2015). In a model course of androgenesis, microspores develop into embryos similar to the zygotic ones (Sangwan and Sangwan-Norreel 1996;Wrobel et al 2011), however in practice, haploid cells may develop into a variety of structures. Among them are embryos with well-formed scutellum, root and shoot apical meristems and coleoptile.…”
Section: Introductionmentioning
confidence: 99%
“…These results also showed that the physical isolation of cells by the deposition of cutin may be a factor that allows the changes in the direction of cell differentiation within the explant 85 . An analysis of the distribution of the low-molecular weight symplasmic tracers (HPTS and uncaged fluorescein) during barley androgenesis indicates the symplasmic isolation of the protodermis from the underlying cells of the late globular embryo stage onwards, and the embryonic organs at the mature stage of development, which allows the conclusion that in androgenic embryos in Hordeum vulgare the existence of symplasmic domains correlates with tissue and organ development 62 . Similar studies were performed on the somatic embryos of Arabidopsis 85 , 98 , 99 .…”
Section: Zygotic and Non-zygotic Embryogenesis—a Good Model For Symplasmic Communication Studiesmentioning
confidence: 99%
“…Much more interesting are the “temporary symplasmic domains,” which consist of cells, or group of cells which only temporally closed PD on the domain border or the movement of molecules through PD is diminished quantitative or qualitative 61 . Sometimes within the domain, subdomains can be distinguished 62 . Temporal domains are more interesting because the analysis of their appearance/disappearance and the mechanisms involved in their function can provide answers to the role of symplasmic domains in plant growth and development and the spatio-temporal correlation between symplasmic domains and cell differentiation 59 …”
Section: Symplasmic Communication/isolation—basic Definitionmentioning
confidence: 99%
“…Among the different mechanisms which control the process of plant development, including zygotic and non-zygotic embryogenesis (somatic embryogenesis and androgenesis), symplasmic communication/isolation is also postulated (Gisel et al, 1999;Kurczyńska et. al., 2007, Wrobel et al, 2011. This process is an important mechanism for the exchange of information between cells within a plant body.…”
Section: Changes In Symplasm During Sementioning
confidence: 99%
“…It was shown for barley androgenic embryos that the symplasmic barrier exists between protodermis and the underlying tissues up to the late globular stage, in the isolation of www.intechopen.com Cellular Markers for Somatic Embryogenesis 323 meristematic cells of the embryo in the transitional and coleoptilar stage, and between the embryo proper and the scutellum and the coleorhizae at the mature stage of the embryo (Wrobel et al, 2011). In the case of Arabidopsis, symplasmic isolation was correlated with the morphogenesis of somatic embryos ( Fig.…”
Section: Changes In Symplasm During Sementioning
confidence: 99%